2019
DOI: 10.1021/acs.est.9b00707
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Permeability Control in the Subsurface via Calcium Silicate Carbonation

Abstract: Efforts to develop safe and effective next-generation energy and carbon-storage technologies in the subsurface require novel means to control undesired fluid migration. Here we demonstrate that the carbonation of calcium silicates can produce reaction products that dramatically reduce the permeability of porous media and that are stable. Most calcium silicates react with CO2 to form solid carbonates but some polymorphs (here, pseudowollastonite, CaSiO3) can react to form a range of crystalline calcium silicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…However, precipitates can be desirable in applications such as geologic carbon storage, where CO 2 trapping through mineralization represents the most secure and permanent form of carbon sequestration (Matter & Kelemen, 2009). Precipitation can also be leveraged for targeted permeability reduction in operations where fluid migration needs to be actively controlled, such as geologic carbon storage and enhanced geothermal energy production (Plattenberger et al, 2019). While our experiments indicated highly reactive reservoirs can promote sudden and extensive precipitation in the presence of reactive fluids that may lead to fracture sealing, observations also suggested that localized precipitates in less reactive systems can serve as effectual proppants that prevent compaction‐driven fracture closure with increasing stress without completely sealing fractures from further flow.…”
Section: Discussionmentioning
confidence: 99%
“…However, precipitates can be desirable in applications such as geologic carbon storage, where CO 2 trapping through mineralization represents the most secure and permanent form of carbon sequestration (Matter & Kelemen, 2009). Precipitation can also be leveraged for targeted permeability reduction in operations where fluid migration needs to be actively controlled, such as geologic carbon storage and enhanced geothermal energy production (Plattenberger et al, 2019). While our experiments indicated highly reactive reservoirs can promote sudden and extensive precipitation in the presence of reactive fluids that may lead to fracture sealing, observations also suggested that localized precipitates in less reactive systems can serve as effectual proppants that prevent compaction‐driven fracture closure with increasing stress without completely sealing fractures from further flow.…”
Section: Discussionmentioning
confidence: 99%
“…XRF maps, such as the one used in the abstract graphic, reveal that CCSHs tend to precipitate along solid interfaces such as sand grains, whereas carbonates tend to precipitate indiscriminately throughout pore bodies. 18 The relative abundance of CaCO 3 to CCSH phases appears to be influenced by at least three factors: (1) The reactivity of the parent silicate (eq 1) is important because pseudowollastonite dissolves congruently, whereas wollastonite dissolves incongruently. 19 Since many of the CCSH mineral phases have Ca:Si ratios of approximately 1, the dissolution of mineral species like wollastonite, that leach calcium selectively (resulting in a solid layer of unreactive silica), do not have the molar ratios needed to produce CCSHs.…”
Section: Synthesis Of Crystalline Calcium Silicate Hydratesmentioning
confidence: 99%
“…It accelerates the dissolution (eq 1), and formation of CaCO 3 may be a Na + can also be incorporated directly in some of the CCSH mineral phases (e.g., eq 4). 18,19 Compressive Strength and Carbon Utilization of Various Cement Types. OPC derives its strength from the hydration of tricalcium and dicalcium silicates (alite and belite) that form amorphous calcium silicate hydrate (CSH) gels, shown in Figure 1a.…”
Section: Synthesis Of Crystalline Calcium Silicate Hydratesmentioning
confidence: 99%
“…Moreover, although the additives of dolomite and wollastonite exhibited similar enhancement effects on CO 2 uptake, they may have different mechanisms. Wollastonite particles can directly react with CO 2 , which can increase the degree of reaction 22,25 . Dolomite cannot react with CO 2 but possibly could act as a seed crystal like calcite in the carbonation process to guide the precipitation of carbonation products on specific crystal surface 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Wollastonite particles can directly react with CO 2 , which can increase the degree of reaction. 22,25 Dolomite cannot react with CO 2 but possibly could act as a seed crystal like calcite in the carbonation process to guide the precipitation of carbonation products on specific crystal surface. 26 The final apparent CO 2 uptake value was a comprehensive result of different promotion effects.…”
Section: Resultsmentioning
confidence: 99%